ANALYSIS OF FACTORS AFFECTING MOTHERS' BEHAVIOR IN THE LINTAS DIARRHEA PROGRAM IN BANGUN REJO VILLAGE IN 2025 - Wahyuni, Retno; Sari, Febriana; Subroto, Edi; Zega, Petra Dian; Nuraisyah, Sitti; Efitasari, Yuni; Hutabarat, Yosefvania Agatha (Yayasan Nuraini Ibrahim Mandiri, 2025)
Background: Diarrhea remains a major public health problem in Indonesia and is a significant cause of morbidity and mortality in young children, especially in areas with limited access to clean water and sanitation. Objective: This study aims to analyze the factors that influence mothers' behavior in implementing the LINTAS Diarrhea program in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency.Method: This analytical cross-sectional study involved 35 mothers of infants selected using purposive sampling. Data were collected using a closed-ended questionnaire and analyzed using the Chi-Square test (p<0.05). Results: The majority of respondents had good knowledge (62.9%), positive attitudes (60.0%), supportive family support (57.1%), and easy access to information (65.7%). Knowledge (p=0.001), attitude (p=0.020), family support (p=0.003), and access to information (p=0.002) were significantly associated with mothers' behavior in LINTAS Diarrhea.Conclusion: Knowledge, attitude, family support, and access to information influence mothers' behavior in the prevention and management of diarrhea.